Accounting for certified emission reductions (CERs) in India: An analysis of the disclosure and reporting practices within the financial statements. Issue 2 (21st October 2019) - Kumar, Praveen; Firoz, Mohammad
Abstract : Purpose: The purpose of this paper is to analyse the certified emission reduction (CERs) disclosure and reporting practices followed by Indian firms. Design/methodology/approach: The study is based on all 131 Indian firms who received the CERs under the CDM of UNFCCC. The content analysis is being used to examine the recognition, measurement, presentation and disclosure of CERs within the financial statements. Findings: The study found that there is generally no uniformity of accounting for CERs. The firms adopted a diversity of accounting practices. More specifically, majority of companies (40.46 per cent) recognised CERs as the other income; a very high non-disclosure rate (91.60 per cent) for valuation of CERs inventories was found as only four companies (3.05 per cent) provided accounting treatment for CERs inventories at lower of cost or net realisable value followed by three companies (2.29 per cent) accounted for these inventories at Net realisable value at the end of the reporting period; similarly, a very high non-disclosure rate (92.36 per cent) for how companies account for expenses incurred in earning these credits was found. Research limitations/implications: The study will be useful for a wide array of audiences ranging from accounting standard setter to the auditors. The present analysis is based on secondary data, as we examined only annual reports of the sample companies to know how they recognise their earned CERs within the financial statements. So, we did not cover the opinions of various key persons of companies like an accountant, auditors etc. which could be a limitation of this study in validating CERs disclosure practices followed by the Indian firms. Originality/value: To the best of the author's knowledge, the present study is a first of its kind to analyse the carbon credit disclosure practices in the context of a developing country.